GROWTH, FLOWERING AND PHOTOSYNTETIC PIGMENTS OF PELARGONIUM × HORTORUM L.H. BAILEY ‘SURVIVOR HOT PINK’ AND ‘GRAFFITI FIRE’ GROWN IN SUBSTRATES CONTAINING SEWAGE SLUDGE COMPOST - Agnieszka Zawadzińska (Journal of Ecological Engineering, 2015)
The aim of this study was to assess usability of composts made of sewage sludge and either straw or leaves used as substrates for growing zonal pelargoniums. The study plants ‘Hot Pink’ cv. of Survivor group and ‘Fire’ cv. of Graffiti group were grown in 5 different substrates. The control substrate was high peat (100%) deacidified with chalk and dolomite up to pH 5.8–6.0 and supplemented with 2.5 g·dm-3 of Azofoska multicomponent fertilizer. The other four substrates contained two types of composts: SSRS – sewage sludge, straw (1:1, v/v) and SSL – sewage sludge, leaves (1:1, v/v), mixed with high peat at two different proportions, 1:3 (v/v) and 1:7 (v/v). Chemical composition of the substrates was investigated and they were supplemented with nitrogen and potassium as recommended for pelargoniums. Plant morphological parameters were evaluated during flowering. They included plant height and diameter, number of shoots and leaves, leaf assimilation area and leaf weight. Leaf chlorophyll and carotenoid content was also estimated. Inflorescence related parameters included inflorescence diameter and inflorescence stem length, number of flowers per inflorescence and flower diameter. All inflorescences formed over 10 weeks of flowering were counted. Plant ornamental value was assessed using a five-score bonitation scale. The investigated composts were found to be useful components of the substrates for zonal pelargonium production. Irrespective of the compost share, the tested substrates significantly affected most of the evaluated morphological traits. The substrate containing the compost made of sewage sludge and straw (SSRS) and peat (1:3, v/v) was found the most beneficial for pelargonium foliage, i.e. the number of leaves, their fresh weight and assimilation area. Leaf chlorophyll and carotenoid content in the pelargoniums grown in the substrates containing either dose of SSRS compost did not differ from the control plants. Substrate type did not affect bonitation score of ‘Survivor Hot Pink’ cultivar. The bonitation score of ‘Graffiti Fire’ cultivar was the highest for plants growing in the substrates with either SSRS or SSL compost plus peat in 1:3 ratio (v/v).